2015
DOI: 10.1371/journal.pone.0136145
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Derived Stem Cells with a Renal Progenitor Phenotype Inhibit Interstitial Fibrosis in Renal Ischemia and Reperfusion Injury in Rats

Abstract: ObjectivesMesenchymal stem cells derived from human amniotic fluid (hAFSCs) are a promising source for cellular therapy, especially for renal disorders, as a subpopulation is derived from the fetal urinary tract. The purpose of this study was to evaluate if hAFSCs with a renal progenitor phenotype demonstrate a nephroprotective effect in acute ischemia reperfusion (I/R) model and prevent late stage fibrosis.MethodsA total of 45 male 12-wk-old Wistar rats were divided into three equal groups;: rats subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 82 publications
2
18
0
Order By: Relevance
“…Authors agree that the higher the dose, the worse the outcome, mostly due to cell emboli formation. The optimal cell concentration range found is 5 × 10 5 − 1 × 10 6 ( 164 , 231 ).…”
Section: Msc Therapy In the Treatment Of Kidney Diseases: State Of Thmentioning
confidence: 96%
See 1 more Smart Citation
“…Authors agree that the higher the dose, the worse the outcome, mostly due to cell emboli formation. The optimal cell concentration range found is 5 × 10 5 − 1 × 10 6 ( 164 , 231 ).…”
Section: Msc Therapy In the Treatment Of Kidney Diseases: State Of Thmentioning
confidence: 96%
“…I/R injury eventually leads to kidney fibrosis, which is the deposition of connective tissue in the renal parenchyma. Studies using hiPSC with renal lineage and amniotic fluid-derived stem cells (AFSC) revealed a decrease in interstitial fibrosis and myofibroblast formation ( 164 , 165 ). In another study using hWJ-MSC the reduction of overall fibrosis was attributed to a HGF/TGF-β shift to HGF ( 170 ).…”
Section: Msc Therapy In the Treatment Of Kidney Diseases: State Of Thmentioning
confidence: 99%
“…MSC-mediated microvesicle release has also been shown to enhance cell survival and attenuate programmed cell death processes ( Bruno et al, 2012 , 2009 ). Overall, numerous studies have demonstrated that exogenous administration of MSCs attenuates renal ischemia-reperfusion injury ( Du et al, 2013 ; Bruno et al, 2009 ; Togel et al, 2005a ; Jiang et al, 2015 ; Duffield and Bonventre, 2005 ; Monteiro Carvalho Mori Da Cunha et al, 2015 ; Duffield et al, 2005 ) and, therefore, may be a potential future renoprotective strategy.…”
Section: Impact Of Iri On Renal Graft Survival: Novel Protective Stramentioning
confidence: 99%
“…These cells presented anti-inflammatory and antiapoptotic effects and inhibited fibrosis in an ischemia-reperfusion model in rats. 14 Because stem/progenitor cells from specific adult tissue generally present limited differentiation potential and its existence in the adult kidney is questionable, preterm neonatal urinary cells (born before completion of nephrogenesis) might be a tissue-specific potent source of progenitors with higher potential compared with adult cells.…”
mentioning
confidence: 99%